Ferroelectric dielectrics integrated on silicon - Defaÿ, Emmanuel (ISTE ; Wiley, 2011)
This book describes up-to-date technology applied to high-K materials for More Than Moore applications, i.e. microsystems applied to microelectronics core technologies. After detailing the basic thermodynamic theory applied to high-K dielectrics thin films including extrinsic effects, this book emphasizes the specificity of thin films. Deposition and patterning technologies are then presented. A whole chapter is dedicated to the major role played in the field by X-Ray Diffraction characterization, and other characterization techniques are also described such as Radio frequency characterization. An in-depth study of the influence of leakage currents is performed together with reliability discussion. Three applicative chapters cover integrated capacitors, variables capacitors and ferroelectric memories. The final chapter deals with a reasonably new research field, multiferroic thin films.